Representasi Komunukasi Identitas Selegbram pada Tren Budaya Pop Kawaii Hijab di Indonesia - Sendy Krisna Puspitasari; Nunuk Endah Srimulyani; Rifdah Fadhillah; Ade Saikhu Sya'Ban (Jurnal Ilmiah Global Education, 2026)
Fashion trends in Japanese popular culture and the representation of identity in Muslim women's communities that combine kawaii outfits and hijabs are the focus of this study. This study uses a qualitative method with a phenomenological approach that aims to understand how Michael Hecht's identity communication theory analyzes the identity of a kawaii hijab by understanding it through four layers: personal layer, endorsement layer, communal layer, and relational layer. Data collection was conducted through in-depth interviews with kawaii hijabers, participatory observation, observation of their activities on social media, and visual content analysis of photos uploaded by kawaii hijabers on Instagram. platform. Samples were selected using purposive sampling. Triangulation of methods and data sources was used in this study to increase the validity of the research findings, verify the findings, and discuss with peers to review interpretations and findings and minimize researcher bias. The results of this study indicate that the existence of kawaii hijab as a fashion trend in Japanese popular culture that can be applied in Indonesia reflects complex identity dynamics, where kawaii hijab women successfully combine elements of religion and popular culture in their appearance.